Dicerandrol B: a natural xanthone dimer induces apoptosis in cervical cancer HeLa cells through the endoplasmic reticulum stress and mitochondrial damage - Gao, Dandan (Onco Targets Ther, 2019)
BACKGROUND: Dicerandrol B is a natural antitumor agent that can be isolated from the endophytic fungus, Phomopsis sp. The present study investigated the effects of dicerandrol B on human cervical cancer HeLa cells. MATERIALS AND METHODS: In this study, dicerandrol B was identified by electrospray ionization mass spectrometry and nuclear magnetic resonance spectroscopy. We used MTT to detect the cell viability. Flow cytometry was used to analyze the apoptosis and cell cycle. Western blot was used to examine the expression of related proteins. RESULTS: Dicerandrol B was isolated from the endophytic fungus Phomopsis sp. The MTT assay and flow cytometry showed that dicerandrol B significantly inhibited HeLa cell viability and induced G2/M cell cycle arrest. Western blot analysis demonstrated that dicerandrol B increased the levels of GRP78, ubiquitin, cleaved PARP, and Bax protein, decreased the levels of PARP and Bcl-2 protein, and caused an increase in the Bax/Bcl-2 ratio in HeLa cells. Dicerandrol B increased the production of ROS in HeLa cells, which was attenuated by the antioxidant N-acetyl-l-cysteine. CONCLUSION: These findings suggest that dicerandrol B induces apoptosis in human HeLa cells, possibly through the endoplasmic reticulum stress and mitochondrial apoptotic pathways. This suggests that dicerandrol B possesses strong anticancer activity in cervical cancer and provides insight into the underlying mechanisms.